Perubahan Politik dan Sosial Budaya Masyarakat Gampong Aceh Di Era Internet–New Media - Umaimah Wahid (Postgraduate of Jayabaya University, 2015)
The Acehnese political communication starts from Gampong and embraces all individual inclusively. The political processes and the Gampong governance (village) in Aceh are held in meunasah which is a learning and community center of the Acehnese society. The research utilizes a constructivism paradigm that is to try to understand, explain and interpret meanings and ongoing social interactions. The governance of the Acehnese society is the first-level governance proven effective in advancing the Acehnese society. The political communicators like kechiek, imeum and tuhapeut govern based on fixed job descriptions without overlapping and violating each other. Internet technology as new media having character provides a new thing for the processing, transmission, reception and response as well as the interactive nature between users of new media audiences and it gives implication in media management change paradigm and the effect of community/audience. The system and structure is a form of the local treasure in which the Acehnese society is developed. Internet causing political and social change in the culture of the gampong.